Islam and the Challenge of Human Rights - Shadi Mokhtari (International Institute of Islamic Thought, 2010)
In Islam and the Challenge of Human Rights, Abdulaziz Sachedina calls for a new conversation between religious and secular forces to achieve an “overlapping consensus” on human rights and its underlying principles. According to him, developing a firm foundation for human rights in Islam is key to reaching such a consensus. Thus after critiquing the contemporary human rights regime and the traditionalist Muslim approach to it, he tries to develop such a theological foundation. Although showing a keen awareness of the numerous tensions between the international human rights framework and the Muslim world’s cultural, social, and political sensibilities, the author posits that some form of notions of individuality, human agency, and human dignity are compatible with the Islamic revelation. Recognizing this provides Islam and the human rights project important “common moral terrain.” ...